2016
DOI: 10.1155/2016/8075432
|View full text |Cite
|
Sign up to set email alerts
|

Tendency to Ingest Foreign Bodies in Mentally Retarded Patients: A Case with Ileal Perforation Caused by the Ingestion of a Teaspoon

Abstract: Introduction. Unintentional foreign body ingestion commonly occurs accidentally in children aged between 3 months and 6 years and at advanced ages or results from psychiatric disorders such as hallucination in patients with mental retardation. Most of the ingested foreign bodies are naturally discharged from the body but some of them may require surgical intervention. Presentation of Case. A 29-year-old mentally retarded female patient was admitted to the emergency service with a two-day history of abdominal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Yildiz et al [38] reported ileal perforation in a patient with mental retardation who had ingested a teaspoon. Gastrointestinal tract complications are also often seen in psychiatric patients as the result of swallowing foreign bodies such as screws, nails, scrap metal, lighters, pegs, and coins.…”
Section: Discussionmentioning
confidence: 99%
“…Yildiz et al [38] reported ileal perforation in a patient with mental retardation who had ingested a teaspoon. Gastrointestinal tract complications are also often seen in psychiatric patients as the result of swallowing foreign bodies such as screws, nails, scrap metal, lighters, pegs, and coins.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body (FB) ingestion is among the commonest emergencies in gastroenterology-endoscopy; this is often involuntary in adults and may be voluntary in psychiatric patients, drug abusers, and elderly and children. [1][2][3][4][5][6][7][8][9][10][11][12][13] The estimated male to female ratio of this phenomenon is 1.5:1, and the FBs differ among the age groups. 1,2,10 The BFs pass beyond the esophagus and resolve spontaneously in up to 90% of cases; the others impact on some segment of the gastrointestinal tract and require interventions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,10 The BFs pass beyond the esophagus and resolve spontaneously in up to 90% of cases; the others impact on some segment of the gastrointestinal tract and require interventions. [1][2][3][4][5][6][7][8][9][10][11][12][13] However, the morbidity and mortality associated with impacted FBs is significant. 2,4,7,11 The commonest sites of impaction are: upper, middle and lower esophagus; stomach; angle of Treitz; ileocecal valve, and appendix.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations